2020
DOI: 10.1101/2020.06.26.173419
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A neural surveyor to map touch on the body

Abstract: Perhaps the most recognizable sensory map in all of neuroscience is the somatosensory homunculus. Though it seems straightforward, this simple representation belies the complex link between an activation in somatosensory Area 3b and the associated touch location on the body. Any isolated activation is spatially ambiguous without a neural decoder that can read its position within the entire map, though how this is computed by neural networks is unknown.We propose that somatosensory cortex implements multilatera… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(23 citation statements)
references
References 135 publications
(206 reference statements)
4
17
0
Order By: Relevance
“…(F(5,185)=0.21, p=.96). Crucially, the pattern of variable errors (Figure 1D) in both tasks displayed the hypothesized inverted U-shape, which was of similar magnitude to what we observed for touch on the arm (8,10). ously observed for localization on the arm (gray line and squares) in (10).…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…(F(5,185)=0.21, p=.96). Crucially, the pattern of variable errors (Figure 1D) in both tasks displayed the hypothesized inverted U-shape, which was of similar magnitude to what we observed for touch on the arm (8,10). ously observed for localization on the arm (gray line and squares) in (10).…”
Section: Resultssupporting
confidence: 83%
“…Analysis of the variable errors (2x6 repeated measures ANOVA) found a significant main effect of hit location (F(5,185)=36.1, p<.001) but no main effect of task (F(1,37)=0.39, p=.54) or an interaction (F(5,185)=0.21, p=.96). Crucially, the pattern of variable errors (Figure 1D) in both tasks displayed the hypothesized inverted U-shape, which was of similar magnitude to what we observed for touch on the arm (8,10). ously observed for localization on the arm (gray line and squares) in (10).…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…Since it is essential to identify the position of a tactile object in order to interact with it, more than a century of research has characterized the perceptual processes underlying tactile localization at a behavioral level ((Badde et al, 2015;Cholewiak and Collins, 2003;Fuchs et al, 2019;Harrar and Harris, 2009;Ho and Spence, 2007;Liu and Medina, 2021;Mancini et al, 2011;Miller et al, 2020;Parrish, 1897;Sadibolova et al, 2018;Stevens, 1992;Weber, 1846); for a review see (Heed et al, 2015)). These studies have identified different spatial codes that are utilized to localize tactile stimuli.…”
Section: Introductionmentioning
confidence: 99%